2022
DOI: 10.3390/separations9110360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Venom Potential of Areca catechu Seed Extract on Bungarus caeruleus Venom

Abstract: Areca catechu seeds and their extract/s are currently used to treat various ailments and infections including snakebites. The purpose of this investigation was to assess the inhibiting/neutralizing effect of ethyl acetate and aqueous ethanolic seed extracts of A. catechu on Bungarus caeruleus (krait) venom. The enzyme activities and their inhibition were evaluated using standard procedures (in vitro). In vivo studies were conducted using chick embryos and murine models. The extracts inhibited hyaluronidase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Subsequent scholarly investigations into the pharmacological properties of AN extracts have revealed their antidepressant, antimicrobial, anti-aging, insecticidal, anti-osteoporotic, hepatoprotective, and anti-inflammatory effects ( Dar et al, 1997 ; Lee and Choi, 1999 ; Pithayanukul et al, 2009 ; Li et al, 2017 ; Jam et al, 2021 ; Sharaf et al, 2021 ; Kweon et al, 2022 ; Puyathorn et al, 2022 ). In a recent study, extracts from arecae semen demonstrated inhibitory effects on snake venom ( More et al, 2022 ). Summarizing modern pharmacological experiments on AN alkaloids and polyphenols has revealed their diverse biological functions, including insecticidal, anti-inflammatory, antimicrobial, hypotensive, anxiolytic, antidepressant, gastrointestinal improvement, and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent scholarly investigations into the pharmacological properties of AN extracts have revealed their antidepressant, antimicrobial, anti-aging, insecticidal, anti-osteoporotic, hepatoprotective, and anti-inflammatory effects ( Dar et al, 1997 ; Lee and Choi, 1999 ; Pithayanukul et al, 2009 ; Li et al, 2017 ; Jam et al, 2021 ; Sharaf et al, 2021 ; Kweon et al, 2022 ; Puyathorn et al, 2022 ). In a recent study, extracts from arecae semen demonstrated inhibitory effects on snake venom ( More et al, 2022 ). Summarizing modern pharmacological experiments on AN alkaloids and polyphenols has revealed their diverse biological functions, including insecticidal, anti-inflammatory, antimicrobial, hypotensive, anxiolytic, antidepressant, gastrointestinal improvement, and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%